PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Hendri Gunawan (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) and investment decisions on firm value in mining sector companies listed on the Indonesia Stock Exchange during the 2013–2017 period. The study employed a quantitative approach using secondary data obtained from corporate financial statements. The sample was selected through purposive sampling based on specific criteria, including listing consistency, availability of audited financial reports, and the publication of CSR reports during the observation period. The dependent variable is firm value, proxied by Price to Book Value (PBV), while the independent variables consist of CSR, measured using a disclosure index, and investment decisions, proxied by the Price Earnings Ratio (PER). The data analysis techniques included descriptive statistics, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination, processed using SPSS version 24. The results indicate that CSR has a positive and significant effect on firm value partially, and investment decisions also have a positive and significant effect on firm value partially. Simultaneously, both variables were proven to have a positive and significant effect on firm value. These findings imply that improving the quality of CSR disclosure and making appropriate investment decisions can enhance investor confidence and strengthen the firm value of mining companies.